Pitch perfect 3 [videorecording (DVD)] - Banks, Elizabeth, 1974-; Kendrick, Anna; Wilson, Rebel; Snow, Brittany, 1986-; Rapkin, Mickey (Universal Pictures Home Entertainment, 2018)
Following their win at the world championship, the now separated Bellas reunite for one last singing competition at an overseas USO tour, but face a group who uses both instruments and voices.